mcr-1 Colistin Resistance in ESBL-Producing Klebsiella pneumoniae, France - Caspar, Yvan (Emerg Infect Dis, 2017)
We report intestinal carriage of an extended-spectrum β-lactamase−producing Klebsiella pneumoniae strain with high-level resistance to colistin (MIC 24 mg/L) in a patient in France who had been hospitalized for fungal meningitis. The strain had the mcr-1 plasmid gene and an inactivated mgrB gene, which are associated with colistin resistance.